Volunteers' knowledge activities at UK music festivals: a hermeneutic-phenomenological exploration of individuals' experiences. Issue 1 (8th February 2016) - Clayton, Diana
Abstract : Purpose: – This paper aims to explore how and why volunteers share knowledge and engage in other related knowledge activities. The paper offers an interpretation of participants' multiple realities to enable a better understanding of managing volunteer knowledge, which ultimately underpins organisational performance and effectiveness. Design/methodology/approach: – A qualitative, hermeneutic phenomenological study of volunteers ( n = 28) at UK music festivals was conducted through in-depth interviews ( n = 9), diaries ( n = 11) or both ( n = 8). This interpretivist approach adopted purposive sampling to recruit participants through (social) media. Findings: – The findings illustrate how and why volunteers share knowledge that is attributed to a successful process of volunteering, which enables effective knowledge management and knowledge reproduction. Where volunteers' motivations are satisfied, this leads to repeat volunteering. Knowledge enablers and the removal of barriers create conditions that are conducive for knowledge sharing, which have similar characteristics to conditions for continuance commitment. Where volunteers do not return, the organisation leaks knowledge. Research limitations/implications: – Although high-quality research standards were maintained, participant self-selection may result in overly positive experiences. Future research might explore the impact on knowledge sharing of negative volunteering experiences. Practical/implications: – Practical recommendations include factors that contribute to effective volunteer co-ordination and volunteering experiences, which are enablers for knowledge sharing. These fall within two categories, namely, areas for continuance (i.e. those aspects that should be maintained because they contribute to effective volunteer co- ordination and experiences) and areas for improvement (i.e. those aspects of volunteer co-ordination that are either currently lacking or require development or enhancement). Originality/value: – This paper's original contribution is demonstrated through the use of hermeneutic phenomenological methods in the exploration of individuals' perspectives of knowledge sharing in the context of temporary organisations. This paper provides value to academics studying knowledge management and volunteer management, and practitioners managing volunteers.